Implementation of Community Economic Empowerment Program on the Coast of Samber Village, Yendidori District, Biak Numfor Regency - Iswahyudi Iswahyudi; Febby Yul Yawan; Asmadianto Asmadianto; Edyanto Edyanto (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2025)
This study aims to describe the implementation of the Community Economic Empowerment Program in the coastal area of Samber Village, Yendidori District, Biak Numfor Regency through the Kalamo Program (Modern Fishermen's Village). The approach used is qualitative descriptive with data collection techniques through in-depth interviews, observations, and documentation. The results of the study show that the implementation of the Kalamo Program has had a positive impact on the coastal community of Samber Village. In terms of improving skills and institutional access, it can be seen that there is training and the formation of cooperatives, although the management still needs to be improved. In terms of natural resource management, some communities have begun to implement more environmentally friendly fishing practices. Meanwhile, the improvement of the quality of life of the community can be seen from the increase in income and the emergence of new business opportunities, although it is not evenly distributed among all fishermen groups. Overall, the implementation of this program has been running, but it is not fully optimal. Further efforts are needed to strengthen institutional capacity, equitable program distribution, and increase socialization so that the empowerment goals can be achieved comprehensively.